Examining the blurred boundaries between medical and recreational cannabis – results from an international study of small-scale cannabis cultivators. (4th May 2019) - Hakkarainen, Pekka; Decorte, Tom; Sznitman, Sharon; Karjalainen, Karoliina; Barratt, Monica J.; Frank, Vibeke Asmussen; Lenton, Simon; Potter, Gary; Werse, Bernd; Wilkins, Chris
Abstract: Aim: To compare characteristics of recreational vs. medical growers in a sample of small-scale cannabis cultivators from 12 countries. Methods: Six thousand eight hundred ninety six respondents who took part in an online survey were divided into three groups as: those who reported growing for recreational use, those cultivating for medical purposes who also reported use of other illegal drugs, and those who reported cultivation for medical use and didn't use other illegal substances. The groups were compared using multinomial logistic regression. Findings: In comparison to recreational growers, the two groups of medical growers included more females, consumed cannabis more frequently, and were more likely to cite health-related motivations for growing. The medical growers without other illicit drug use shared some of the same features with the medical growers with illicit drug use, but in comparison to both other groups, they were older, used less alcohol and tobacco, and were less likely to be involved in illicit activities other than drug crimes. Conclusions: Findings suggest that claims of medical use are not simply an attempt to justify personal cannabis consumption, but do at least partly reflect a genuine belief in medical benefit. However, those growing cannabis for medical reasons form a heterogeneous group of people.